Carbon Monoxide Levels in The Lungs of Workers in City of Makassar in 2023 - Sri Wahyuni; Maidin, Alimin; Jamal, Hudriani; Sirajuddin, Nursaidah; Andi Mariani; Henny Karmila; Hamdani, Musyarrafah (Universitas Airlangga, 2024)
Background: Smoking is an unhealthy behavior that can cause health problems that affect the damage to the body's organs, namely the lungs. Measurement of carbon monoxide levels using a smoke analyzer is an alternative for early detection of health problems in the lungs due to smoking. Aims: This study aims to determine smoking behavior and the amount of cigarette consumption with carbon monoxide levels in the lungs of workers in Makassar City. Research Methods: This study design is a quantitative analysis, with a cross-sectional study method, using secondary data from the smoking cessation program, Makassar City Health Office, with random sampling techniques obtained from 157 men aged 40-60 years. Secondary data obtained are the results of carbon monoxide (CO) measurements using a smoke analyzer by blowing on the device. Processing of data using SPSS 25 with the chi-square test. Results: The results showed that there were people who had a habit of smoking very high levels of carbon monoxide in the lungs (61.9%) with a p-value = 0.000 and the number of cigarettes consumed during one year of very high levels of carbon monoxide in the lungs (72.0%) with a p-value = 0.000. Conclusion: there is a relationship between smoking habits and the number of cigarettes consumed by workers who smoke. Preventive interventions such as lung CO examination are an assessment of risk factors for health problems.